For the feathered villagers urban habitat conservation of Avifaunal Species Pycnonotus Goiavier and Dicaeum Australe in Nayong Pilipino Parañaque through wildlife inclusive design - Lloren, Katrice Gale S.
Progress in the country comes with urbanization that consequently affects the urban wildlife and fragments the remaining green patches. Therefore, past studies aimed to conserve habitats in urban landscape as they realized that urban wildlife is important to the remaining ecosystem. These studies emphasized that when these faunal species are also prioritized, its ecological role will continue and will contribute to strengthening the urban ecology. Such examples are the urban birds that are seed dispersers throughout the city. However, habitat conservation in parks surrounded by large and highly urbanized developments is not often tackled. This study aims to propose landscape interventions for habitat conservation of chosen avian species in the urban environment of Bagong Nayong Pilipino Urban Forest Park located at the heart of Entertainment City, Parañaque. The research aims to select the appropriate target species which are the Pycnonotus goiavier and the Dicaeum australe and to study their behavior and life cycle requirements in the area, the landscape conditions, disturbances such as pollution and noise, the future land use, and the users’ needs. The findings will then be used for redesigning the site into a wildlife inclusive park for habitat conservation and ecological improvement. It is hypothesized that if a wildlife inclusive park is designed, then target birds are protected and thus ecological improvement in the urban landscape is achieved. The results and outputs of the study will show the significant impact of birds when their needs are also addressed in Nayong Pilipino amidst other human demands and urban developments.